Food tree species consumed during periods of food shortage in Burkina Faso and their threats - Vinceti, B.; Termote, Céline; Thiombiano, N.; Agundez, D.; Lamien, Niéyidouba (Instituto Nacional de Investigacion y Tecnologia Agraria y Alimentaria (INIA), 2018)
Aim of study: Edible products from tree species were identified in Burkina Faso and their contribution to the diet in the lean season was assessed. The main threats affecting most consumed food tree species were also documented.Area of study: Six villages across two phytogeographic regions of Burkina FasoMaterial and methods: Focus group discussions and semi-structured interviews, including a 7-day dietary intake recall targeting women; semi-structured interviews targeting key male informants.Main results: The number of edible tree products consumed was found to vary according to phytogeographic region and ethnic group. A few tree species played a disproportionally greater role in the diet and were characterized by very high frequency of consumption by the majority of households in both phytogeographic regions and across ethnicities: Adansonia digitata, Parkia biglobosa and Vitellaria paradoxa. These species are not critically endangered at country level but they are perceived as scarcely available at local level. Considering that the main threats on priority tree species (fires, drought, pest and diseases) vary across regions, to maintain sustainable sources of nutrients in the landscape, mitigation measures should be diversified and adapted to local pressures.Research highlights: Priorities for conservation are emerging clearly, but research efforts should also target underutilized tree species for their potential to diversify nutrient-poor diets.